Diphtheria, tetanus, poliomyelitis, yellow fever and hepatitis B seroprevalence among HIV1-infected migrants. Results from the ANRS VIHVO vaccine sub-study. Issue 38 (11th September 2015) - Mullaert, Jimmy; Abgrall, Sophie; Lele, Nathalie; Batteux, Frederic; Slama, Lilia Ben; Meritet, Jean-Francois; Lebon, Pierre; Bouchaud, Olivier; Grabar, Sophie; Launay, Odile; ,
Abstract: Background: Few data are available on the seroprotection status of HIV1-infected patients with respect to vaccine-preventable diseases. Objective: To describe, in a population of HIV1-infected migrants on stable, effective ART therapy, the seroprevalence of diphtheria, poliomyelitis, tetanus, yellow fever antibodies and serostatus for hepatitis B, and to identify factors associated with seroprotection. Vaccine responses against diphtheria, tetanus, poliomyelitis and yellow fever were also studied. Methods: Sub-Saharan African patients participating in the ANRS-VIHVO cohort were enrolled prior to travel to their countries of origin. Serologic analyses were performed in a central laboratory before and after the trip. Univariate and multivariate logistic regression was used to identify factors associated with initial seroprotection. Results: 250 patients (99 men and 151 women) were included in the seroprevalence study. Median age was 45 years (IQR 39-52), median CD4 cell count was 440/μL (IQR 336-571), and 237 patients (95%) had undetectable HIV1 viral load. The initial seroprevalence rates were 69.0% (95%CI 63.2–74.7) for diphtheria, 70.7% (95%CI 65.0–76.3) for tetanus, and 85.9% (95%CI 81.6–90.2) for yellow fever. Only 64.4% (95%CI 58.5–70.3) of patients had protective antibody titers against all three poliomyelitis vaccine strains before travel. No serological markers of hepatitis B were found in 18.6% of patients (95%CI 13.7–23.3). Patient declaration of prior vaccination was the only factor consistently associated with initial seroprotection. Conclusions: We found a low prevalence of seroprotection against diphtheria, poliomyelitis, tetanus and hepatitis B. HIV infected migrants living in France and traveling to their native countries need to have their vaccine schedule completed.